The French Shore Problem in Newfoundland : An Imperial Study - Thompson, Frric F. (Book collections on Project MUSE., 1961)
The story of the French shore problems is not merely concerned with international treaties which both Britain and France interpreted to their advantage, but is also much of the story of Newfoundland's emergence from Imperial proscription.